2015
DOI: 10.1039/c4nj01552e
|View full text |Cite
|
Sign up to set email alerts
|

One pot domino reaction accessing γ-nitroesters: synthesis of GABA derivatives

Abstract: Michael addition of 1,3-dicarbonyl compounds to nitrostyrenes is efficiently promoted by hydrotalcite [Mg-Al] to afford the respective g-nitrodicarbonyl adducts. Differently, the addition of Meldrum's acid leads to a direct access of g-nitroesters through a one pot domino process. GABA derivatives (+/À)-phenibut and (+/À)-baclofen were readily synthesized from the respective nitro adducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Speculating about the reaction mechanism, we presumed that the alcoholic solvent is able to promote the opening and transesterification of the Meldrum's acid moiety in the Michael adduct initially formed. 25 The adduct 6a was not isolated during the multicomponent process. Thus, we focused our efforts on its isolation and characterization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Speculating about the reaction mechanism, we presumed that the alcoholic solvent is able to promote the opening and transesterification of the Meldrum's acid moiety in the Michael adduct initially formed. 25 The adduct 6a was not isolated during the multicomponent process. Thus, we focused our efforts on its isolation and characterization.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that HT combined with Meldrum's acid resulted in the formation of γ-nitroesters directly. 25 The activity of HT was attributed to the increase in the basicity of this material by the formation of mixed magnesium and aluminium oxides after thermal treatment that we called HT [Calc. ] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste minimization without any side reactions, use of non-toxic and inexpensive catalysts and recyclability of catalyst are other advantageous features of this procedure. Survey over several reaction parameters (solvent, temperature, and time) was reported by Naciuk et al [98] who investigated Michael reaction for the synthesis of γ-aminobutyric acid (GABA). Another study on the Michael additions of 2-methylcyclohexane-1,3-dione, 2-acetylcyclopentanone, and 2-acetylcyclohexanone to methyl vinyl ketone interestingly revealed that Mg/Al molar ratio was strongly related to the catalytic performance, pointing out a nonlinear correlation between the Mg content and catalytic activity [99].…”
Section: 9 X For Peer 10 Of 43mentioning
confidence: 99%
“…Due to the utility of β-aryl-γ-lactams as key synthetic intermediates for the synthesis of γ-amino acids [17] in conjunction with their biological activity, several methods have been reported for the synthesis of γ-lactams [18,19,20,21,22]; however, it is yet highly desirable to develop convenient and milder protocols for its preparation, especially with various substitution patterns and enantiomerically purity. In this paper, we report an efficient synthesis of a series of β-aryl-γ-lactams and its resolution by derivatization with ( S )-Naproxen.…”
Section: Introductionmentioning
confidence: 99%